Analisis Faktor Penyebab Luka pada Bencana Banjir dan Tanah Longsor di Kota Manado - Ratuliu, Gladis; Geneo, Martinus; Tiwatu, Filia Veronica (STIKES Ngesti Waluyo, 2023)
Disasters such as floods, landslides, earthquakes, and so on can cause health problems including injuries and skin disorders such as open or closed wounds to skin infections. The Manado City Government had made efforts to deal with floods and landslides through BNPB, one of which was by evacuating residents from areas prone to flooding and landslides. This study aimed to determine the factors that cause injuries in the floods and landslides that occurred in January-February 2021 in Manado City. This study was a quantitative descriptive study with non-probability sampling technique, with a total of 44 respondents. The inclusion criteria were Manado City residents and had injuries or wound due to floods or landslides. Exclusion criteria was residents who already had injuries before the disaster. The result of this study were: most respondents were in the early and late elderlies age group, were male, were inside of their houses when the disaster occurred. Most type of injuries occurred due to irritation of floodwater. It can be concluded that there was no significant relationship between age and location when the disaster occurred and the wound etiology and there was a significant relationship between gender, which was male, and wound etiology. It is recommended that residents in disaster-prone areas be given education about disaster preparedness to prevent injuries when a disaster occurred.